Deep-level study of Ga(In)P(NAs) alloys grown on Si substrates. (August 2016) - Baranov, A I; Kleider, J P; Gudovskikh, A S; Darga, A; Nikitina, E V; Egorov, A Yu
Abstract: Defect properties of Ga(In)P(NAs) layers with different composition were studied by admittance spectroscopy. For nitrogen content layers the defect level with energy of 0.44-0.47 eV, which related to nitrogen incorporation into GaP, was observed. Its concentration is lower for GaPNAs layers compared to GaPN/InP due to better compensation by arsenic than by indium in lattice of GaP. Other defect level with energy of 0.30 eV was detected in GaPAs and GaPN/InP layers. Likely, the both observed defects in GaPAs and GaPN/InP have the same nature.